The Influence of Transparency, Village Government Accountability, Internal Control, Good Governance and Human Resource Competence in Bondowoso Village - Kurnia Fajrin Mega Utami; HP Agustin; Lia Rachmawati (ARTOKULO : Journal of Accounting, Economic and Management, 2024)
This study aims to analyze the influence of Transparency, Village Government Accountability, Internal Control, Good Governance and Human Resource Competence on Village Fund Management in Jambesari District. The type of research used is quantitative research. The data used is primary data with data collection techniques through questionnaires. The population in this study were all Village Apparatus in Jambesari District. The data collection technique used was the purposive sampling method and used a sample of 56 respondents. The data analysis method used was data instrument testing, classical assumption testing, determination coefficient (R2), hypothesis testing and multiple linear regression analysis with the help of IBM SPSS Statistics 27. The results of the study indicate that partially the variables Transparency (X1), Internal Control (X3), and Human Resource Competence (X5) do not have a significant effect on Village Fund Management (Y). However, the variables of Village Government Accountability (X2) and Good Governance (X4) have a significant effect on Village Fund Management (Y). The higher the level of accountability and implementation of Good Governance, the better the management of village funds in Jambesari District Village